The music of the Lord of the rings films : a comprehensive account of Howard Shore's scores - Adams, Dough (Alfred Music, 2010)
Presents the complete account of the making of the Lord of the Rings trilogy music score, and includes extensive music examples, original manuscript scores, and glimpses into the creative process from the composer. Includes a comprehensive description, including musical examples, of the score's leitmotifs. The acc. CD presents music for the films that, due to alternate versions or subsequent compositions, has never before been released; includes a 2-part conversation between the author and the composer